A systematic review on thalassaemia screening and birth reduction initiatives cost to success - Abd Rahim, Azrin Syahida; Abd. Rahim, Nour El Huda; Jaafar, Safurah (Malaysian Medical Association, 2024)
Introduction: Thalassaemia has been prevalent with high morbidity and mortality rates since 1925. Although there is a lack of systematic review on the costs of prevention that has yielded reductions in thalassaemia prevalence, this review will show a widespread presence of complex but effective strategies in reducing national thalassaemia prevalence. Materials and Methods: A systematic search was conducted using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA 2020). Designated keywords were combined with search functions and Boolean operators in databases like Scopus, Web of Science and several other search databases. Results: The search identifed 5425 potential articles. Most countries reported a decline in thalassaemia prevalence after implementing intervention programmes for several decades. The screening methods, however, varies, and the speed of reductions depends on the type of screening approach that involves blood screening of adolescence and antenatal mothers and, in some countries, includes termination of pregnancy. In addition, the cost of these initiatives varies as it was challenging to find a common denominator. However, the endpoint concedes that the cost of screening, although substantial, would be offset by the cost of reduction of cases. In some countries, cost-effectiveness analyses have been reported to support the initiatives of thalassaemia screening and prevention in the long run. Conclusion: The results showed significant variations in success rates with a significant reduction in the prevalence of Thalassaemia. Most successful are countries with comprehensive and aggressive prevention and control programmes that engaged with lab screening, counselling, and termination of pregnancy as a package.